2013
DOI: 10.1128/cvi.00121-13
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T Cell Adoptive Immunotherapy as a Treatment for Nasopharyngeal Carcinoma

Abstract: c Epstein-Barr virus (EBV) is associated with nasopharyngeal carcinoma (NPC). We assess the safety and tolerability of adoptive transfer of autologous cytotoxic T lymphocytes (CTLs) specific for the EBV latent membrane protein (LMP) in a patient with recurrent NPC. After infusion, the majority of pulmonary lesions were no longer evident, although the primary tumor did not regress. CASE REPORT In 2002, a middle-aged man (42 years old) was diagnosed with stage IV (T4 N2c M1) Epstein-Barr virus (EBV)-positive und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…The fact that EBV-specific CTL from peripheral blood of NPC patients can be reactivated ex vivo brings up a trend of adoptive autologous CTL therapy [6, 28]. Although adoptive CTL therapy in NPC gained effectiveness in phase II clinical trial [28], the specificity of CTLs activated by EBV-transformed lymphoblastoid cell lines (LCLs) are still under evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that EBV-specific CTL from peripheral blood of NPC patients can be reactivated ex vivo brings up a trend of adoptive autologous CTL therapy [6, 28]. Although adoptive CTL therapy in NPC gained effectiveness in phase II clinical trial [28], the specificity of CTLs activated by EBV-transformed lymphoblastoid cell lines (LCLs) are still under evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The strong association of NPC with EBV makes viral antigen-targeted immunotherapy an attractive treatment modality [5]. Adoptive transfer of autologous EBV-specific CTL has proven effective in metastatic or locally recurrent NPC patients [6]. Meanwhile, efficacies of DNA vaccines carrying various combination of EBV antigens are also under evaluation [79].…”
Section: Introductionmentioning
confidence: 99%
“…The most straightforward approach has used defined HLA-restricted synthetic peptide epitopes to generate CTL either using a single stimulation with peptide or following repeated stimulation with peptide coated LCL [59]. In Phase I clinical studies this approach has shown some evidence of disease regression with a recent case report demonstrating clearance of pulmonary lesions following CTL infusion, although no impact on the primary tumor was detectable [60]. To broaden the HLA coverage in these targeted approaches other clinical studies have employed recombinant vectors to deliver either whole antigen or polyepitope constructs designed to provide broad HLA coverage while restricting the potential risks associated with the oncogenicity of the LMP antigens [61,62].…”
Section: Review Smith and Khannamentioning
confidence: 99%
“…Moreover, when the plasma samples of the patients have been collected a peak in the EBV DNA have been observed which is the proof of the fact that the NPC cells have undergone lysis by the action of these infused CTLs. It is also interesting to note that there is possibility that the CTLs have better access to lungs when infused (Abbas et al, 2007;Kenter et al, 2008;Kenter et al, 2009;Lutzky et al, 2014).…”
Section: Post Transplant Lymphoproliferative Disease (Ptld) and Nasopmentioning
confidence: 99%